Bifunctional Magnetite–Gold Nanoparticles for Magneto-Mechanical Actuation and Cancer Cell Destruction - Garanina, Anastasiia S.; Efremova, Maria V.; Machulkin, Alexey E.; Lyubin, Evgeny V.; Vorobyeva, Natalia S.; Zhironkina, Oxana A.; Strelkova, Olga S.; Kireev, Igor I.; Alieva, Irina B.; Uzbekov, Rustem E.; Agafonov, Viatcheslav N.; Shchetinin, Igor V.; et al. (Magnetochemistry, 2022)
Magnetite–gold dumbbell nanoparticles are essential for biomedical applications due to the presence of two surfaces with different chemical natures and the potential combination of magnetic and plasmonic properties. Here, the remote actuation of Fe3O4-Au hybrid particles in a rotating (1 Hz, 7 mT), static (7 mT) or pulsed low-frequency (31 Hz, 175 mT, 30 s pulse/30 s pause) magnetic field was studied. The particles were synthesized by a high-temperature wet chemistry protocol and exhibited superparamagnetic properties with the saturation magnetization of 67.9 ± 3.0 Am2 kg−1. We showcased the nanoparticles’ controlled aggregation in chains (rotating/static magnetic field) in an aqueous solution and their disaggregation when the field was removed. The investigation of nanoparticle uptake by LNCaP and PC-3 cancer cells demonstrated that Fe3O4-Au hybrids mainly escaped endosomes and accumulated in the cytoplasm. A significant fraction of them still responded to a rotating magnetic field, forming short chains. The particles were not toxic to cells at concentrations up to 210 μg (Fe3O4) mL−1. However, cell viability decrease after incubation with the nanoparticles (≥70 μg mL−1) and exposure to a pulsed low-frequency magnetic field was found. We ascribe this effect to mechanically induced cell destruction. Overall, this makes Fe3O4-Au nanostructures promising candidates for intracellular actuation for future magneto-mechanical cancer therapies.